Investigation on Graphitization, Surface Functional Groups, and Oxidation Behavior of Soot Particulate Along Exhaust Pipe of Gasoline Direct Injection Engine - Zhiyuan Hu; Li Yin; Jiayi Shen; Zhangying Lu; Piqiang Tan; Diming Lou (Energies)
This study investigated the changes in graphitization, surface functional groups, and oxidation behavior of soot particulates along an exhaust pipe of a gasoline direct injection (GDI) engine using Raman spectroscopy, X-ray photoelectron spectroscopy (XPS), and thermogravimetric analysis (TGA). The main findings were as follows: The oxidation temperature of soot particulates was between 300 °C and 650 °C. The soot particulates generated for a higher engine load or near the exhaust valve tended to exhibit a lower ratio of a disordered graphite lattice and amorphous carbon. As the engine load increased, the graphitization degree of soot particulates became higher and the content of oxygen-containing functional groups and oxidation activity of soot particulates became lower, meaning that it became more difficult for the soot particulate to be oxidized. Under a light load, as the engine speed increased, the disorder of the edge array of soot particles became higher, the content of oxygen-containing functional groups and oxidation activity became higher, and the soot particles were more easily oxidized. On the other hand, with an increase in engine speed under a heavy load, the microscopic disorder of soot particulates decreased; lower contents of oxygen-containing functional groups and oxidation activity were observed and oxidation became more difficult. Moreover, with increasing transportation distance along the exhaust pipe of the GDI engine, the graphitization degree, content of surface functional groups, and oxidation behavior of soot particulate presented changes similar to the increasing engine speed under a light load, and oxidation became easier.